Incentives to Learn - Kremer, Michael; Miguel, Edward; Thornton, Rebecca; Ozier, Owen (World Bank, Washington, DC, 2012)
The authors report results from a randomized evaluation of a merit scholarship program for adolescent girls in Kenya. Girls who scored well on academic exams received a cash grant and had school fees paid. Girls eligible for the scholarship showed significant gains in academic examination scores (average gain 0.15 standard deviations). There was considerable sample attrition and no significant program impact in the smaller of the two program districts, but in the other district girls showed large gains (average gain 0.22-0.27 standard deviations), and these gains persisted one full year following the competition. There is also evidence of positive program externalities on learning-boys (who were ineligible for the awards) also showed sizable average test gains. Both student and teacher school attendance increased in the program schools.